THE INVESTIGATION OF THE INFLUENCE OF TRAFFIC LIGHTS CYCLE DURATION ON THE CROSSROAD TRANSPORT SITUATION (BY THE EXAMPLE OF TULA) - A. Y. Harabadj (Вестник СибАДИ, 2017)
The issue of opportunities to improve the efficiency of intersections in the changing conditions of the traffic load of the city is considered. The influence of the duration of the time cycles of neighboring traffic lights on the length of the vehicle queue that appears between the traffic lights is studied. It is shown that the formation of the queue has a dynamic character, which should be investigated within the framework of the nonlinear dynamics approach.